Sistem Pendeteksi Kualitas Buah Naga Berbasis Iot ( Internet of Things ) - Rizqo Direr Ramadlan; M. Taqijjuddin Alawiy; Oktriza Melfazen (Science Elektro, 2022)
The need for vitamin intake is very important for the body. Moreover, vitamins that come from fruits. With the increasing number of enthusiasts, some farmers began to explore planting dragon fruit plants with red color (Hylocereus Costaricensis). With that, a color and weight detector is needed to make it easier for farmers to get good results. Basically the tool works using the Arduino UNO microcontroller. At first, the TCS230 sensor detects red or green. Then the sensor will send a command to the servo motor to run the closing command when the sensor detects a green color. After passing the TCS230 sensor, then the dragon fruit will be carried on the conveyor to be weighed in the load cell sensor. After the weighing reaches a maximum load of 3000 grams, the relay will automatically turn on to stop the movement of the conveyor. To show and control the weighing results, NodeMCU will send commands and results to be displayed on the smartphone via the Blynk app. The load cell sensor has a weighing success accuracy of 99.7% and only has an error of 0.3% and the TCS230 sensor functions well.